Chemical Compositions and Insecticidal Activities of the Essential Oils from Several Medicinal Plants Against the Cotton Whitefly, Bemisia tabaci - Sertkaya, Erdal; Kaya, Kamuran; Soylu, Soner (Asian Journal of Chemistry, 2010)
Chemical compositions and insecticidal activities of plant essential oils obtained from medicinal plants, thyme (Thymbra spicata subsp. spicata), rosemary (Rosmarinus officinalis), fennel (Foeniculum vulgare) and laurel (Laurus nobilis), were investigated against adults of cotton whitefly (Bemisia tabaci Gen.). Volatile phase effects of different concentrations of the essential oils used were used to determine insecticidal activities. Major compounds found in essential oils of thyme, rosemary, fennel and laurel were carvacrol (70.9 %), borneol (20.4 %), transanethole (82.8 %) and 1,8-cineole (35.5 %), respectively. Laboratory bioassay results indicated that all essential oils caused adult mortality of whitefly at different concentrations that are not phytotoxic to the host plant. All essential oils showed insecticidal activities in a dose-dependent manner. Essential oil of thyme had a marked insecticidal activity against whitefly adults. Adult viability was totally affected by thyme, laurel, fennel and rosemary at the concentrations of 5.0, 20.0, 30.0 and 30.0 μg mL-1 air, respectively. Estimated mean lethal concentrations (LC50) of the essential oils of thyme, laurel, fennel and rosemary were 0.44, 1.82, 7.06 and 2.86 μg mL-1 air, respectively. The results of the present study concluded that plant essential oils could be useful in promoting research aiming at the development of new agent for pest control from the plants with medicinal values.